Combination of organic acids benzoate, butyrate, caprylate, and sorbate provides a novel antibiotics-independent treatment option in the combat of acute campylobacteriosis - Du, Ke; Foote, Minnja S.; Mousavi, Soraya; Buczkowski, Agnes; Schmidt, Sebastian; Peh, Elisa; Kittler, Sophie; Bereswill, Stefan; Heimesaat, Markus M. (Frontiers in Microbiology, 2023)
The food-borne Gram-negative bacterial pathogen Campylobacter jejuni may cause the acute enterocolitis syndrome campylobacteriosis in infected humans. Given that human C. jejuni infections are rising globally which hold also true for resistance rates against antibiotic compounds such as macrolides and fluoroquinolones frequently prescribed for the treatment of severe infectious enteritis, novel antibiotics-independent therapeutic strategies are needed. Distinct organic acids are well known for their health-beneficial including anti-microbial and immunomodulatory properties. In our present study, we investigated potential pathogen-lowering and anti-inflammatory effects of benzoic acid, butyric acid, caprylic acid, and sorbic acid either alone or in combination during acute murine campylobacteriosis. Therefore, secondary abiotic IL-10-/- mice were perorally infected with C. jejuni strain 81-176 and subjected to a 4-day-course of respective organic acid treatment. On day 6 post-infection, mice from the combination cohort displayed slightly lower pathogen loads in the duodenum, but neither in the stomach, ileum nor large intestine. Remarkably, the clinical outcome of C. jejuni induced acute enterocolitis was significantly improved after combined organic acid treatment when compared to the placebo control group. In support, the combinatory organic acid treatment dampened both, macroscopic and microscopic inflammatory sequelae of C. jejuni infection as indicated by less colonic shrinkage and less pronounced histopathological including apoptotic epithelial cell changes in the colon on day 6 post-infection. Furthermore, mice from the combination as compared to placebo cohort exhibited lower numbers of innate and adaptive immune cells such as neutrophilic granulocytes, macrophages, monocytes, and T lymphocytes in their colonic mucosa and lamina propria, respectively, which also held true for pro-inflammatory cytokine secretion in the large intestines and mesenteric lymph nodes. Notably, the anti-inflammatory effects were not restricted to the intestinal tract, but could also be observed systemically given pro-inflammatory mediator concentrations in C. jejuni infected mice from the quadruple organic acid treatment that were comparable to basal values. In conclusion, our in vivo study provides first evidence that an oral application of distinct organic acids in combination exhibits pronounced anti-inflammatory effects and hence, constitutes a promising novel antibiotics-independent therapeutic strategy in the combat of acute campylobacteriosis.